2009
DOI: 10.1371/journal.pmed.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Preventing Loss to Follow-up in HIV Treatment Programs: A Côte d'Ivoire Appraisal

Abstract: Based on data from West Africa, Elena Losina and colleagues predict that interventions to reduce dropout rates from HIV treatment programs (such as eliminating copayments) will be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 46 publications
1
75
1
Order By: Relevance
“…Several studies have shown the cost-effectiveness of HIV linkage and retention in care programs implemented in the USA (Creese, Floyd, Alban, & Guinness, 2002;Hogan, Baltussen, Hayashi, Lauer, & Salomon, 2005;Holtgrave, 1998;Kim et al, 2015;Losina et al, 2009;Marseille et al, 2009Marseille et al, , 2012Renaud, Basenya, De Borman, Greindl, & Meyer-Rath, 2009;Walker, 2003). The evaluators of Health Resources and Services Administration's Special Projects of National Significance found program costs of $241,565 ($393 per patient) (Gopalappa, Farnham, Hutchinson, & Sansom, 2012).…”
mentioning
confidence: 99%
“…Several studies have shown the cost-effectiveness of HIV linkage and retention in care programs implemented in the USA (Creese, Floyd, Alban, & Guinness, 2002;Hogan, Baltussen, Hayashi, Lauer, & Salomon, 2005;Holtgrave, 1998;Kim et al, 2015;Losina et al, 2009;Marseille et al, 2009Marseille et al, , 2012Renaud, Basenya, De Borman, Greindl, & Meyer-Rath, 2009;Walker, 2003). The evaluators of Health Resources and Services Administration's Special Projects of National Significance found program costs of $241,565 ($393 per patient) (Gopalappa, Farnham, Hutchinson, & Sansom, 2012).…”
mentioning
confidence: 99%
“…In addition to low coverage rates, the expansion of PMTCT services has been accompanied by significant rates of loss to follow-up (LTFU), defined as being absent from a health centre for more than three months following a scheduled appointment or service, among pregnant and post-partum women living with HIV. Efforts to prevent LTFU would both improve patient survival rates and be cost effective, according to an assessment conducted in Côte d'Ivoire (Losina et al, 2009).…”
mentioning
confidence: 99%
“…The majority of those identified were [32], is likely to be cost-effective given savings derived from sustained treatment. In concentrated epidemics situated in high-and middle-income settings, far more is needed to identify effective test and treat campaigns, particularly among female sex workers (FSW) and MSM-with young MSM being a specific priority.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these studies served as examples of innovative strategies to diagnose hard-to-reach clients in resource-limited settings. In the interest of optimizing retention in HIV care in such settings, Losina et al [32] estimated that eliminating antiretroviral therapy (ART) copayments and charges for opportunistic infections, along with personnel training and providing meals and travel reimbursements for clients, would be cost-effective.…”
Section: Cost-effective Interventions By Cascade Stage and Settingmentioning
confidence: 99%